Interpreter Education And Training In Yemen: A Case Study - Mohammed Ahmed Barakat, Eman Mohammed (2015)

(untitled)
Pendidikan dan latihan merupakan dua cabang pembelajaran; pendidikan berkait rapat dengan pemerolehan ilmu pengetahuan, dan pembangunan intelek, manakala latihan pula bertujuan memperoleh kemahiran khusus bagi melaksanakan tugasan yang diberikan dengan sebaik mungkin. Sebagaimana bidang-bidang lain, pendidikan dan latihan diperlukan dalam pengikhtisasan penterjemah dan jurubahasa. Program pendidikan dan latihan jurubahasa bermatlamat mengembangkan kemahiran dan pengetahuan yang diperlukan untuk menginterpretasi, dan untuk menyemai kesedaran terhadap tatalaku jurubahasa yang baik dan memantapkan keahlian sebagai pengamal dalam profesion ini. Di Yaman, pendidikan dan latihan jurubahasa ditawarkan menerusi satu atau dua kursus dalam program terjemahan. Tiada program yang direka khusus untuk melatih bakal jurubahasa. Education and training are two facets of learning; education is about gaining knowledge and developing intellect, whereas training is undertaken for the purpose of acquiring a specific skill to perform adequately a given task. Education and training are necessary for the professionalisation of translators and interpreters, as it is the case with other disciplines. The aims of interpreter education and training programmes are to develop the skills and knowledge required to interpret, and to develop an awareness of suitable conduct and membership as practitioners of a profession. In Yemen, interpreter education and training is offered as part of translation programmes in the form of two or three courses. There are no programmes designed specifically to train interpreters want-to-be. The aim of this study is to draw a complete picture of interpreter education and training in the Yemeni context which covers major educational issues including curriculum components, teaching and learning practices, and assessment procedures. This broad aim is achieved by conducting a case study of interpreter education and training offered at the University of Science and Technology which is the first university in Yemen to offer interpreter education and training at a bachelor’s degree level. To answer research questions, a mixed-method approach is adopted for the purpose of collecting data from different sources, and converging these data via triangulation.